The spatial distribution of crime and population density in Saudi Arabia. Issue 1 (February 2018) - Algahtany, Mofza; Kumar, Lalit; Barclay, Elaine; Khormi, Hassan
Abstract This study examined the relationship between crime and place across the 13 provinces of Saudi Arabia using geographic information systems techniques based on population density, identifying and visualising the spatial distributions of national and regional crime rates for drug crimes, theft, murder, assault, alcohol and 'outrageous crimes' (offences against Islam) over a 10-year period from 2003 to 2012. Social disorganisation theory was employed to guide the study and explain the diversity in patterns in crime across the country. The highest rates of overall crimes were identified in the Northern Border and Jizan areas, located in the north and south of the country, respectively, while the East Area has the lowest crime rate. Most drug offences occurred in Northern Borders and Jizan, high rates of theft were recorded in Northern Borders, Jouf and Makkah, while the highest rates of homicide occurred in Asir.